Studies on the Structural and Optical Properties of AgIn1-XGaXSe2 (0 ≤ x ≤ 1.0) thin Films - Chowdhury, FA; Begum, J; Quadir, L; Hasan, SM Firoz (Journal of Bangladesh Academy of Sciences, 2010)
Polycrystalline thin films of AgIn1-XGaXSe2 (AIGS) with varying x (0 ≤ x ≤ 1.0) have been grown onto glass substrates by stacked elemental layer (SEL) deposition technique in vacuum ( 10-6 mbar). The thickness of the films was kept constant at 500 nm measured on line by frequency shift of quartz crystal. The films were annealed in situ at 300°C for 15 minutes. Structural and optical properties of the films were ascertained by X-ray diffraction (XRD) and UV-VIS-NIR spectrophotometry (photon wavelength ranging between 300 and 2500 nm) respectively. The diffractogram indicates that these films are polycrystalline in nature. The optical transmittance spectra reveal a maximum transmission of 85.91% around 1100 nm of wavelength for x = 0.2. A sharp absorption region is evident from the transmittance spectra that indicate a standard semiconducting nature of the films. The abruptness at the fundamental edge is more distinct in the film with x = 0.2. Optical transmittance, reflectance and thickness of the films were utilized to compute the absorption coefficient, band gap energy and refractive index of the films. The optical band gap is found to be direct-allowed. The band gap energy value, found from this study ranging between 2.3 to 2.4 eV, is very close for different gallium content films. The refractive indices increase almost linearly with photon wavelength range between 1300 and 1500 nm. DOI: 10.3329/jbas.v33i2.4098 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 2, 151-157, 2009